Abandonment of Patient in Emergency Department of Tertiary Care Hospital of Eastern Nepal – a Case Study - Chaudhary, Ritesh; Bhandari, Rabin; Jirel, Sunil; Shrivastav, Vijay; Bhandari, Rupak (Journal of BP Koirala Institute of Health Sciences, 2020)
Introduction: With increasing of workload of emergency room employees, many of the community’s emergency hospitals are now facing another challenge, i.e. the abandonment of patient in emergency Department. It seems undesirable in most hospital service settings due to loss of revenue and ill-will. The hospital’s staffs feel that they have no option but to keep those sufferers until a further plan can be made. It presents a dilemma for the staffs of Emergency and for the hospital administrators as well. The current case report presents an abandoned patient in Emergency Department of B. P. Koirala Institute of Health Sciences (BPKIHS). Case Report: A 70-year old male brought by police and was left abandoned in emergency ward of BPKIHS in altered conscious state. The patient was managed in emergency ward with conservative management nearly for six weeks. Conclusion: The problem is multidimensional, is in conflict of the concept towards achievement of Millennium Development Goals (MDGs) and a challenge to social security.